Flexural Capacities and Stress Block Parameters for High-Strength Concrete Column - A Antonius (Dinamika Teknik Sipil: Majalah Ilmiah Teknik Sipil, 2012)
Flexural behaviour of reinforced high-strength concrete columns is studied in this paper. Tests of 12 high-strength reinforced concrete columns under eccentric loading were conducted, with test parameters included the concrete strength, longitudinal reinforcement ratio, load eccentricities and lateral reinforcement characteristics i.e: spacing and volumetric ratio. Concrete strength used were around of 50 and 70 MPa. From this study, the main result shows that curvature ductility increase with increasing volumetric ratio or reduction of tie spacing for lateral reinforcement. Comparison between stress block parameter models developed by many researchers with the test results was evaluated. It is found that the model adopted in the Indonesian National Standard (SNI 03-2847-2002) and ACI need to be modified before they can be utilized in the flexural design of structures made of high-strength concrete.